Mycotoxins in Ethiopia: A Review on Prevalence, Economic and Health Impacts - Mamo, Firew Tafesse (Toxins (Basel), 2020)
Mycotoxigenic fungi and their toxins are a global concern, causing huge economic and health impacts in developing countries such as Ethiopia, where the mycotoxin control system is inadequate. This work aimed to review the occurrences of agriculturally essential fungi such as Aspergillus, Fusarium, and Penicillium and their major mycotoxins in Ethiopian food/feedstuffs. The incidents of crucial toxins, including aflatoxins (B1, B2, G1, G2, M1), fumonisins (B1, B2), zearalenone, deoxynivalenol, and ochratoxin A, were studied. The impacts of chronic aflatoxin exposure on liver cancer risks, synergy with chronic hepatitis B infection, and possible links with Ethiopian childhood malnutrition were thoroughly examined. In addition, health risks of other potential mycotoxin exposure are also discussed, and the impacts of unsafe level of mycotoxin contaminations on economically essential export products and livestock productions were assessed. Feasible mycotoxin mitigation strategies such as biocontrol methods and binding agents (bentonite) were recommended because they are relatively cheap for low-income farmers and widely available in Ethiopia, respectively. Moreover, Ethiopian mycotoxin regulations, storage practice, adulteration practice, mycotoxin tests, and knowledge gaps among value chain actors were highlighted. Finally, sustained public awareness was suggested, along with technical and human capacity developments in the food control sector.